New metabolically stabilized analogues of lysophosphatidic acid: agonists, antagonists and enzyme inhibitors. (26th October 2005) - Prestwich, G.D.; Xu, Y.; Qian, L.; Gajewiak, J.; Jiang, G.
Abstract : Lysophosphatidic acid (LPA) is a metabolically labile natural phospholipid with a bewildering array of physiological effects. We describe herein a variety of long-lived receptor-specific agonists and antagonists for LPA receptors. Several LPA and PA (phosphatidic acid) analogues also inhibit LPP (lipid phosphate phosphatase). The sn -1 or sn -2 hydroxy groups have been replaced by fluorine, difluoromethyl, difluoroethyl, O -methyl or O -hydroxyethoxy groups to give non-migrating LPA analogues that resist acyltransferases. Alkyl ether replacement of acyl esters produced lipase and acyltransferase-resistant analogues. Replacement of the bridging oxygen in the monophosphate by an α-monofluoromethylene-, α-bromomethylene- or α, α-difluoromethylenephosphonate gave phosphatase-resistant analogues. Phosphorothioate analogues with O -acyl and O -alkyl chains are potent, long-lived agonists for LPA1 and LPA3 receptors. Most recently, we have (i) prepared stabilized O -alkyl analogues of lysobisphosphatidic acid, (ii) explored the structure–activity relationship of stabilized cyclic LPA analogues and (iii) synthesized neutral head group trifluoromethylsulphonamide analogues of LPA. Through collaborative studies, we have collected data for these stabilized analogues as selective LPA receptor (ant)agonists, LPP inhibitors, TREK (transmembrane calcium channel) K + channel agonists, activators of the nuclear transcription factor PPAR-γ (peroxisome-proliferator-activated receptor-γ), promoters of cell motility and survival, and radioprotectants for human B-cells.